Investigation of InterphaseProperties in Polymer nanocomposites - Gaurav Pant* (International Journal of Advanced Science and Technology, 2020)
Polymer nanocomposites are contemporarily one of the most fascinating materials in the manufacturing sector. These are synthesized by doping nano filler particles into the base polymer. On doing this, interphase formation occurs in the material. Interphase is just the interface between the nanoparticle and the base matrix. The mechanical properties are quite complicatedly distributed in this interphase area. In this work, possibility of the variation of mechanical properties in this interphase is analyzed. The distribution of mechanical properties is investigated based on the power laws governing the interphase. It is indeed required to get the idea of interphase property variation, as it is directly responsible for the final properties of polymer nanocomposite. The significant improvement in the properties of nanocomposites is obtained because of this peculiar interphase formation. But the region of interphase is quite complicated. So extensive literature survey is required for proceeding ahead